The Development of Research-Based Learning Devices to Enhance Grade X Students’ Critical Thinking Skills in Learning Physics - Ajeng Suci Misndari; R. Wulan; Usmeldi Usmeldi (Postgraduate School, Universitas Negeri Padang, 2020)
Physics learning in schools had not fully trained students' critical thinking skills. The reason was that learning has not been centered on students, and the learning devices used by teachers had not encouraged the active involvement of students in learning and finding their knowledge. Learning model that present a learning environment by emphasizing the central role of students is research-based learning. This learning model guides students to form hypotheses, collect and process data, and draw conclusions by discussing in groups. The involvement and activeness of students will encourage students' critical thinking activities. The aim of this study is the development of research-based learning devices with practical, valid, and effective criteria to improve students' critical skills on impulse and momentum material. The development model used is ADDIE from Branch. Research data was validity data, practicality data, and effectiveness data. The research instruments used were validation sheets, practicality sheets, and effectiveness sheets. This study had an output to create research-based learning devices with valid, effective, and very practical categories to enhance students' critical thinking skills.